Aktivitas aglutinin dari beberapa jenis rumput laut di Teluk Manado - Jenny Kumajas (Jurnal Kimia Fullerene, 2017)
Manado Bay waters have a high diversity of seaweed. This study aims to find the seaweed in Manado Bay waters that have aglutinin activity. Seaweed samples were taken in Manado Bay. After cleaned and identified, the samples were extracted. The extract was tested on human red blood cells (erythrocytes) of 4 types (A, B, O and AB) with controls made without addition of extracts. The activity of agglutinin is determined by the agglutination titer of the highest dilution which causes cell agglutination. Agglutinin activity of each type of seaweed was tested at various temperature and pH. Among five species of seaweed that were tested, only three were agglutinated human red blood cells types A, B, O and AB. Halimeda macroloba and H. taenicola did not show any aglutinin activity. Based on the research, it can be concluded that Ulva fasciata seaweed, Halymenia durvillaei and Laurencia obtusa from Manado Bay waters have agglutinin activity.